A Cadaveric Study of Portal Vein Termination and Its Surgical Relevance - Shilpa N. Gosavi; Surekha D. Jadhav; Rajendra S. Garud (Journal of Krishna Institute of Medical Sciences University, 2017)
Background: The Portal Vein (PV) is formed from the convergence of the superior mesenteric and splenic vein posterior to the neck of the pancreas. At porta hepatis it divides into right and left main branches. Aim and Objectives: The study was conducted to note the level and types of termination of portal vein in Indian livers. Material and Methods: The level of termination of portal vein was classified as extrahepatic, capsular and intrahepatic in seventy seven normal adult human cadaveric livers. The type of termination of PV was noted and classified according to the classification suggested by Atasoy and Ozvurek. Length of extrahepatic part of right and left branch of portal vein was measured with the help of digital vernier caliper. Results: Termination of PV was observed as extrahepatic in 89.61%, Intrahepatic in 3.89% and capsular in 6.49%. Bifurcation was observed in 97.41% and trifurcation in 2.49%. Mean length of the extrahepatic part of right branch of portal vein was observed as 1.38 ± 0.38 cm while length of left branch of portal vein was observed as 1.91 ± 0.73cm. Conclusion: Pre-surgical awareness of variant portal venous anatomy is important before graft procurement in liver transplantation, hepatic tumor resection, placement of Transjugular Intrahepatic Porto-systemic Shunts (TIPS) and PVembolization.